Evaluasi Program Teaching Factory dalam Membentuk Budaya Mutu di SMK - Cahyani, Dominica Rila Setyo; Miyono, Noor (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
Teaching factory learning (TEFA) is a production/service-based vocational school learning concept that refers to standards and procedures that apply in industry, and is carried out in an atmosphere similar to that which occurs in industry. Students not only carry out learning activities at school, but also practice (basic competencies) and work (applying their competencies) in industry over a relatively long period of time. Teaching factory learning is expected to produce graduates who suit the needs of the business and industrial world (DUDI). Good and quality education is the basis for further development and progress. Quality in the field of education includes the quality of input, process, output and outcome. Educational quality assurance must be carried out independently and consistently by educational units, therefore it is necessary to build a culture of school quality so that educational goals can be achieved.School quality culture is an important factor in education to shape students into human beings with noble character, honesty, responsibility, optimism, courage, skill, cooperative behavior, tenacity, discipline and integrity. Quality Culture is a value system of an organization that produces environmental conditions that are conducive to the formation of continuous improvement in terms of quality. Quality Culture consists of values, traditions, procedures and expectations that prioritize quality. TEFA is one of the vocational school strategies for building a school culture of quality that will shape character and attitudes of responsibility and professionalism.This research aims to describe the findings from scientific journal articles regarding TEFA Evaluation in Vocational Schools through a literature review. It is hoped that this research can become a reference and consideration for policy makers to carry out improvements and outreach to other vocational schools so that they can implement TEFA well and efficiently. Search for research journal data using the Google Scholar database by applying the keywords "TEFA evaluation in vocational schools" and "TEFA implementation in vocational schools". Journal articles are limited to those published since 2017 but there are no restrictions on the use of language or research methodology used. This literature study used 13 articles that had gone through author screening. The results of this research show that the TEFA Evaluation has been carried out well, but there are still obstacles that need better improvement in the future.